1988
DOI: 10.1111/j.1365-2494.1988.tb02158.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of drainage on herbage growth and soil development

Abstract: The effects of drainage on the yield of perennial ryegrass (Lolium perenne) swards grown for silage, and on soil development under grassland, were studied between 1982 and 1985.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…No routine measurements of root distribution were made in the present study during the experimental period, but subsequent measurements reveal very similar root weight distributions with depth in drained and undrained soils, as were observed by Baker et at. (1988).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…No routine measurements of root distribution were made in the present study during the experimental period, but subsequent measurements reveal very similar root weight distributions with depth in drained and undrained soils, as were observed by Baker et at. (1988).…”
Section: Discussionsupporting
confidence: 76%
“…Dowding (1981) suggested that artificial drainage was likely to increase the rate of N mineralization through increased soil aerobicity, and rates of wetting and drying, thus increasing the supply of N on drained plots. Baker et al (1988) also concluded that the main benefit from drainage to the growth of herbage was enhanced N 'recovery'. These authors imply, however.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This disturbance will certainly include damage induced by the mechanical stripping and replacement of the medium, and may also entail prolonged storage in stockpiles. While these processes may not adversely reduce the availability of soil P and K (Scullion, 1994b;Chapman and Younger, 1995), they may change many of the soil physical qualities, including bulk density, structure and drainage, (Abdul-Kareem and McRae, 1984;Baker et al, 1988;King, 1988). However, perhaps the greatest damage will be inflicted on the soil N cycle.…”
Section: Soil Nutrient Availabilitiesmentioning
confidence: 99%